2014
DOI: 10.1128/mcb.01580-13
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA MRUL Promotes ABCB1 Expression in Multidrug-Resistant Gastric Cancer Cell Sublines

Abstract: bMultidrug resistance (MDR) is the most common cause of chemotherapy failure in gastric cancer (GC) treatment; however, the underlying molecular mechanisms remain elusive. Long noncoding RNAs (lncRNAs) can be involved in carcinogenesis, but the effects of lncRNAs on MDR are poorly understood. We show here that the lncRNA MRUL (MDR-related and upregulated lncRNA), located 400 kb downstream of ABCB1 (ATP-binding cassette, subfamily B, member 1), was significantly upregulated in two multidrug-resistant GC cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 48 publications
0
89
0
2
Order By: Relevance
“…Increasing studies have revealed that lncRNAs have important influence in tumorigenesis, metastasis, and prognosis and drug resistance of gastric cancer [1]. While the functional role and molecular mechanism of many GCassociated lncRNAs remain undetermined, recent studies revealed that several lncRNAs are associated with GC progression, such as H19, FENDRR, and MRUL [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have revealed that lncRNAs have important influence in tumorigenesis, metastasis, and prognosis and drug resistance of gastric cancer [1]. While the functional role and molecular mechanism of many GCassociated lncRNAs remain undetermined, recent studies revealed that several lncRNAs are associated with GC progression, such as H19, FENDRR, and MRUL [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the function of uc009yby.1 in renal cells was investigated using two siRNAs to inhibit uc009yby.1 expression, revealing that this lncRNA could enhance renal cell proliferation; this suggests that uc009yby.1 may be a novel therapeutic target for ccRCC. Numerous studies have indicated that certain lncRNAs have aberrant expression profiles in various kinds of tumors, such as gastric (15)(16)(17), colon (18,19), esophageal (20)(21)(22) and liver (23) cancers. Yu et al (12) recently reported on a class of lncRNAs that are aberrantly expressed in ccRCC cells, in which multiple lncRNAs were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…One more study conducted by Ying Wang et al indicated that the lncRNA-MRUL, MDR-related lncRNA, was significantly upregulated in two multidrugresistant GC cell sublines, SGC7901/ADR and SGC7901/ VCR. Furthermore, the relation between the expression levels of MRUL and growth inhibition rates of GC cell treated with chemotherapy drugs or a poor prognosis for GC patients were significantly negative correlation [43].…”
Section: Gastric Cancermentioning
confidence: 98%